Hepatitis B vaccination in adolescents living in Campinas, São Paulo, Brazil - Priscila Maria Stolses Bergamo Francisco; Maria Rita Donalisio; Filomena de Jesus Oliveira Gabriel; Marilisa Berti de Azevedo Barros (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
INTRODUCTION: Viral hepatitis is an important public health problem in Brazil and around the world. OBJECTIVE: To evaluate vaccination coverage against hepatitis B in adolescents and to identify the associated factors and reasons for non-adherence. METHODS: A cross-sectional population-based study with sampling by clusters and in two stages, carried out from records of 702 adolescents aged 11 to 19 years old, non-institutionalized, living in an urban area of Campinas, São Paulo, Brazil, in 2008/2009. The data were obtained from the Health Survey in the city of Campinas (ISACamp). RESULTS: The prevalence of vaccination (3 doses) was 72.2%. An independent and negative association with the vaccine was observed for the adolescents who were not born in the municipality. The orientation of a health care provider was positively and significantly associated with vaccination. The main reasons for non-adherence were the lack of orientation and not considering the vaccine necessary. Socioeconomic factors, health behaviors and conditions did not restrict the access to vaccination, but the coverage was below the target established by the Ministry of Health in Brazil. CONCLUSION: Health education programs, addressing the importance of vaccination to prevent the disease; strategies to actively reach out adolescents that did not complete the schedule; as well as orientation from the health care professional about the benefits of the vaccine to the adolescents, parents and guardians can extend the vaccination coverage.